A Model of the Institutionalization of Corruption During the Rebuilding Process. (3rd March 2020) - Nuristani, Sami; Vanhove, Adam J.
Abstract : This article offers a model describing the process by which corruption becomes institutionalized in post-conflict nations. The process model integrates multiple theoretical perspectives to propose key enabling factors that promote corrupt behavior: societal instability and uncertainty, cultural characteristics that encourage acquiescence among the public, and the inflow of considerable but poorly accounted for foreign aid. Moreover, the model proposes that it takes relatively few opportunists to experience positive consequences resulting from corrupt behavior for others to imitate such behavior. Increased imitation across the public sector serves to legitimize and subsequently institutionalize corrupt behavior in post-conflict nations. Recommendations for preventing and minimizing the effects of each enabling factor are presented, with the expectation that removing opportunity and creating negative consequences for corrupt behavior will reduce the likelihood of such behavior being imitated. Theoretical implications of this model are also discussed, as are recommendations for testing model propositions.